Antiepileptic Drugs Elevate Astrocytic Kir4.1 Expression in the Rat Limbic Region - Mukai, Takahiro; Kinboshi, Masato; Nagao, Yuki; Shimizu, Saki; Ono, Asuka; Sakagami, Yoshihisa; Okuda, Aoi; Fujimoto, Megumi; Ito, Hidefumi; Ikeda, Akio; Ohno, Yukihiro (Frontiers in Pharmacology, 2018)
Inwardly rectifying potassium (Kir) channel subunits Kir4.1 are specifically expressed in astrocytes and regulate neuronal excitability by mediating spatial potassium buffering. In addition, it is now known that astrocytic Kir4.1 channels are closely involved in the pathogenesis of epilepsy. Here, to explore the role of Kir4.1 channels in the treatment of epilepsy, we evaluated the effects of the antiepileptic drugs, valproate, phenytoin, phenobarbital and ethosuximide, on Kir4.1 expression in astrocytes using immunohistochemical techniques. Repeated treatment of rats with valproate (30-300 mg/kg, i.p., for 1-10 days) significantly elevated the Kir4.1 expression levels in the cerebral cortex, amygdala and hippocampus. Up-regulation of Kir4.1 expression by valproate occurred in a dose- and treatment period-related manner, and did not accompany an increase in the number of astrocytes probed by glial fibrillary acidic protein (GFAP). In addition, repeated treatment with phenytoin (30 mg/kg, i.p., for 10 days) or phenobarbital (30 mg/kg, i.p., for 10 days) also elevated Kir4.1 expression region-specifically in the amygdala. However, ethosuximide (100 mg/kg, i.p., for 10 days), which can alleviate absence but not convulsive seizures, showed no effects on the astrocytic Kir4.1 expression. The present results demonstrated for the first time that the antiepileptic drugs effective for convulsive seizures (valproate, phenytoin, and phenobarbital) commonly elevate the astrocytic Kir4.1 channel expression in the limbic regions, which may be related to their antiepileptic actions.